Subthalamic and thalamic local field potential recordings from patients with cervical dystonia - Wiest, C; Torrecillos, F; Morgante, F; Pereira, E; Tan, H (University of Oxford, 2023)
This data set contains data that were used in Wiest et al., 2022 (https://doi.org/10.1002/mds.29302).